Complex formation dynamics in a single-molecule electronic device - Wen, Huimin; Li, Wengang; Chen, Jiewei; He, Gen; Li, Longhua; Olson, Mark A.; Sue, Andrew C.-H.; Stoddart, J. Fraser; Guo, Xuefeng (Science advances, 2016)
The formation dynamics of a host-guest complex is successfully investigated in graphene-based single-molecule electronic devices. Single-molecule electronic devices offer unique opportunities to investigate the properties of individual molecules that are not accessible in conventional ensemble experiments. However, these investigations remain challenging because they require (i) highly precise device fabrication to incorporate single molecules and (ii) sufficient time resolution to be able to make fast molecular dynamic measurements. We demonstrate a graphene-molecule single-molecule junction that is capable of probing the thermodynamic and kinetic parameters of a host-guest complex. By covalently integrating a conjugated molecular wire with a pendent crown ether into graphene point contacts, we can transduce the physical [2]pseudorotaxane (de)formation processes between the electron-rich crown ether and a dicationic guest into real-time electrical signals. The conductance of the single-molecule junction reveals two-level fluctuations that are highly dependent on temperature and solvent environments, affording a nondestructive means of quantitatively determining the binding and rate constants, as well as the activation energies, for host-guest complexes. The thermodynamic processes reveal the host-guest binding to be enthalpy-driven and are consistent with conventional 1 H nuclear magnetic resonance titration experiments. This electronic device opens up a new route to developing single-molecule dynamics investigations with microsecond resolution for a broad range of chemical and biochemical applications.